PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP TURNOVER INTENTION DI BANK DBS CENTRA WORLD JAKARTA (CWJ) JAKARTA SELATAN - Rozzy, Fachrur; Riyanto, Setyo (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aimed to analyze the effect of leadership style on turnover intention, analyze the effect on turnover intention of motivation and analyze the effect on of leadership style and motivation on turnover intention at DBS Bank in Jakarta. The design of this study was conclusive that consisted of descriptive and causal ie direct survey of the sample of the population using questionnaires. By using the formula Tabachnick and Fidell (Boduszek, 2014) samples obtained are a number of 105 respondents from population 1,500 employees at DBS Bank in Jakarta. The analysis of data using multiple linear regression analysis using SPSS Version 22.0. Results of the study is the leadership style of positive + 0.718 and significant 0.000 effect on turnover intention, influence employee motivation effect on negative – 0.093 and significant 0.022 on turnover intention, style of leadership and employee motivation effect on turnover intention. The regression equation obtained from this research is Y = 1,358 + 0,718X1 - 0,093X2 + e with great influence 43.6% while 56.4% is influenced by other variables outside the research